Oxidative Stress and Neurodegeneration: Insights and Therapeutic Strategies for Parkinson's Disease - Erjola Bej; Patrizia Cesare; Anna Rita Volpe; Michele d'Angelo; Vanessa Castelli (MDPI AG, 2024)
Parkinson's disease (PD) is a progressive neurodegenerative condition marked by the gradual deterioration of dopaminergic neurons in the substantia nigra. Oxidative stress has been identified as a key player in the development of PD in recent studies. In the first part, we discuss the sources of oxidative stress in PD, including mitochondrial dysfunction, dopamine metabolism, and neuroinflammation. This paper delves into the possibility of mitigating oxidative stress as a potential treatment approach for PD. In addition, we examine the hurdles and potential of antioxidant therapy, including the challenge of delivering antioxidants to the brain and the requirement for biomarkers to track oxidative stress in PD patients. However, even if antioxidant therapy holds promise, further investigation is needed to determine its efficacy and safety in PD treatment.